1978
DOI: 10.1042/cs055263s
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Therapy in Patients above Age 60 Years (Fourth Interim Report of the European Working Party on High Blood Pressure in Elderly: EWPHE)

Abstract: 1. A total of 450 hypertensive patients above the age of 60 years have entered the double-blind multicentre trial of the European Working Party on High blood pressure in Elderly (EWPHE). After stratification and randomization half were treated with one capsule daily containing 25 mg of hydrochlorothiazide and 50 mg of triamterene and half were given placebo. In those receiving active treatment, if blood pressure control was not adequate they were given a second capsule and if necessary up to 2 g of methyldopa/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In the double-blind placebo-controlled trial conducted by the European Working Party on High Blood Pressure in the Elderly [2,8,30], the patients of the activetreatment group received hydrochlorothiazide plus triamterene, to which, in 35% of the patients, ámethyldopa was added [2,8,30]. During follow-up, serum creatinine concentration increased in both treatment groups, but the increase was already more pronounced in the actively treated group after 3 months (15.9 ìmol/l; compared with 1.8 ìmol/l; P , 0.001) [2,8,30]. With incidence rates of 33.3 and 9.8 events per 1000 patient-years, the risk of mild renal dysfunction (serum creatinine concentration at least 180 ìmol/l) was 23% greater (CI 12±35%) in actively treated patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the double-blind placebo-controlled trial conducted by the European Working Party on High Blood Pressure in the Elderly [2,8,30], the patients of the activetreatment group received hydrochlorothiazide plus triamterene, to which, in 35% of the patients, ámethyldopa was added [2,8,30]. During follow-up, serum creatinine concentration increased in both treatment groups, but the increase was already more pronounced in the actively treated group after 3 months (15.9 ìmol/l; compared with 1.8 ìmol/l; P , 0.001) [2,8,30]. With incidence rates of 33.3 and 9.8 events per 1000 patient-years, the risk of mild renal dysfunction (serum creatinine concentration at least 180 ìmol/l) was 23% greater (CI 12±35%) in actively treated patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…At present, diuretics are generally used as first-line treatment (Amery et al, 1978), and their safety is satisfactory when adequate clinical and laboratory monitoring are done at regular intervals (Forette et al, 1982b). However, such monitoring is constraining to the patient and may lead to inadequate compliance, which in turn can give rise to serious complications (Editorial, 1978).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…In BBB [ 16 ], we could not extract all-cause mortality data because it was not indicated in the paper. In EWPHE [ 17 ], we used the number from the intention-to-treat analysis. Regarding stroke, there were five differences compared with the Ettehad paper (Supp.…”
Section: Methodsmentioning
confidence: 99%
“…In JATOS [ 20 ], we subtracted the number of TIA. In EWPHE [ 17 ], we used the numbers from the intention-to-treat analysis. In the Hunan Province study [ 21 ], we used the data indicated in the original publication.…”
Section: Methodsmentioning
confidence: 99%